DOI: 10.17077/etd.emxxrt83
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the first year of college on undergraduates' development of altruistic and socially responsible behavior

Abstract: 1The present study examines the effects of first-year college experiences on undergraduate students' development of altruistic and socially responsible behavior -a critical college outcome that leads to significant public or external benefits and support.Furthermore, this study examines whether the effects of first-year college experiences on altruistic and socially responsible behavior vary between first-generation and non-firstgeneration students. To guide the study's investigation, human, social, and cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 84 publications
(103 reference statements)
0
9
0
Order By: Relevance
“…Such interactionssustained in a context of reflection-may provide the cognitive challenge and social support necessary for ethical and prosocial development. Consistent with such a view, studies suggest that education is one of the strongest predictors of altruism (Padgett, 2011;Putnam, 2000). Musil (2009) has argued that there are currently three important reform elements in higher education: diversity, global learning, and civic engagement.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Such interactionssustained in a context of reflection-may provide the cognitive challenge and social support necessary for ethical and prosocial development. Consistent with such a view, studies suggest that education is one of the strongest predictors of altruism (Padgett, 2011;Putnam, 2000). Musil (2009) has argued that there are currently three important reform elements in higher education: diversity, global learning, and civic engagement.…”
Section: Discussionmentioning
confidence: 94%
“…Social capital theory may provide a related explanation of our findings that study abroad, service-learning, diversity interactions and active learning experiences predict prosocial outcomes. Putnam (2000) and Padgett (2011) emphasize the role of social capital-especially forms that engage persons in new social groups-in fostering altruism. Higher education is uniquely situated to engage students in novel social contexts of reciprocity, providing opportunities to experience new world views and care for those they come to know.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also a time when many young people experience anxiety, stress and a decreased sense of personal wellbeing (Eagan, et al, 2015;American College Health Association, 2015). An abundance of research has shown how important the first-year experience is for the development of not just academic and intellectual skills but for the formation of the students' emotional, social, physical and spiritual wellbeing (Upcraft and Gardner, 1989;Padgett, 2011;Bowman, 2010). Consequently, the first year presents an important opportunity for faculty and staff to engage with the students and help them build life-long cognitive and learning skills, a sense of responsibility and altruism, as well as critical life skills (Pascarella & Terenzini, 2011;Padgett 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The federal government determines student's eligibility to receive this money based on their completion of the Free Application for Federal Student Aid (FAFSA). Due to the explicit requirements for students to receive this money, past research studies found this question to be a sufficient proxy for SES (Padgett, 2011;Salisbury, Paulsen & Pascarella, 2011). The institution also provided students' ACT score or SAT equivalent score.…”
Section: Background and Pre-college Characteristicsmentioning
confidence: 99%